Effects of Aroma Head Therapy on Stress and Brain Wave Change Using EEG - Jaeyeon Jeong; Sangsik Lee; Jeehun Jang; Hyonjin Bang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This research studied aroma head therapy on 15 women to observe stress improvement and brain wave responses using EEG. The experiment lasted for two weeks. The experimental method was conducted by measuring the brain waves using EEG before and after the aroma head therapy. SPSS 20.0 statistical program was used for analysis. The amplitude of alpha waves before and after aroma head therapy decreased in both left and right brains. Compared to the amplitude before the massage, the brain wave amplitude of the right brain notably resulted in a decrease. The physical stress index in both left and right brains decreased after aroma head therapy compared to the level before the massage. There was no difference in the mental stress index before and after the massage therapy of the aroma head therapy. Thus, the experiment proved that aroma head therapy has a close relationship in relieving physical stress and bringing psychological stability to middle-aged women. Based on the results, the appropriate use of aromatherapy on the human body shall contribute to maintaining a healthy life and promoting psychological and physical stability.